2015
DOI: 10.1515/eces-2015-0017
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation Of A Spent Metalworking Fluid With Auto- And Allochthonous Bacterial Consortia

Abstract: Spent mineral oil-based metalworking fluids are waste products of the machining processes and contribute substantially to the global industrial pollution with petroleum oil products. Wastewaters containing oily emulsions are ecologically hazardous and thus a variety of methods have been implemented to prevent these effluents from affecting the natural environment. Most of these methods rely upon physical-chemical treatment and phase separation; however, none of them proved to be effective enough to meet tighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…ZB-01 contains strains of bacteria naturally occurring in the environment and specializing in the breakdown of organic pollutants. Their population decreases as petroleum products decompose, allowing to develop typical soil microflora (Kaszycki et al 2011). However, to check if there are any effects that may arise from the circulation of ZB-01 in the soil, also the unpolluted soil was treated by ZB-01.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ZB-01 contains strains of bacteria naturally occurring in the environment and specializing in the breakdown of organic pollutants. Their population decreases as petroleum products decompose, allowing to develop typical soil microflora (Kaszycki et al 2011). However, to check if there are any effects that may arise from the circulation of ZB-01 in the soil, also the unpolluted soil was treated by ZB-01.…”
Section: Methodsmentioning
confidence: 99%
“…ZB-01 biopreparation is a microbial preparation which has been widely used to initiate and stimulate biodegradation of petroleum-derived substances in contaminated waters and soils. We chose it because its usefulness in decomposition of petroleum-derived contaminants has been already confirmed by many studies (Petryszak et al 2008, Kaszycki et al 2010, Kaszycki et al 2011, Kaszycki et al 2015. Finally, we analyzed the relationships between Sitona spp.…”
Section: Introductionmentioning
confidence: 99%
“…Study of biodegradability of organic constituents of the oil/water emulsion obtained from a metal-processing waste stream was carried out in paper [12]. The conducted study showed that oil/water emulsion is non-toxic to bacterial consortia, therefore it was colonized with indigenous microorganisms.…”
Section: Environmental and Climate Technologiesmentioning
confidence: 99%
“…Study of biodegradability of organic constituents of the oil/water emulsion obtained from a metal-processing waste stream was carried out in paper [29]. The conducted study showed that oil/water emulsion is non-toxic to bacterial consortia, therefore it was colonized with indigenous microorganisms.…”
Section: Introductionmentioning
confidence: 99%